Effects of Somatic Mutations in the C-Terminus of Insulin-Like Growth Factor 1 Receptor on Activity and Signaling. (14th June 2012) - Craddock, Barbara P.; Miller, W. Todd
Abstract : The insulin-like growth factor I receptor (IGF1R) is overexpressed in several forms of human cancer, and it has emerged as an important target for anticancer drug design. Cancer genome sequencing efforts have recently identified three somatic mutations in IGF1R: A1374V, a deletion of S1278 in the C-terminal tail region of the receptor, and M1255I in the C-terminal lobe of the kinase catalytic domain. The possible effects of these mutations on IGF1R activity and biological function have not previously been tested. Here, we tested the effects of the mutations on the in vitro biochemical activity of IGF1R and on major IGF1R signaling pathways in mammalian cells. While the mutations do not affect the intrinsic tyrosine kinase activity of the receptor, we demonstrate that the basal (unstimulated) levels of MAP kinase and Akt activation are increased in the mutants (relative to wild-type IGF1R). We hypothesize that the enhanced signaling potential of these mutants is due to changes in protein-protein interactions between the IGF1R C-terminus and cellular substrates or modulators.